2020
DOI: 10.1088/2053-1591/abae26
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and magnetic properties of chromium doped cobalt ferrite nanotubes

Abstract: Chromium (Cr) doped cobalt ferrite (Co1−xCrxFe2O4:x = 0.0, 0.02, 0.04, 0.06, 0.08, 0.1, denoted as to CCFO) hollow nanotubes were synthesized by electrospinnig method followed by, calcining treatment at 700 °C in air. The samples exhibited a single phase cubic spinel phase. The lattice constant of the samples was found to initially decreased and thereafter increases with increased of Cr content. The morphology analysis indicated that the samples displayed a disordered arrangements of hollow structures and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…After x = 0.3, the a 0 rises with increasing Cr content. The rise in the a 0 for a higher concentration of Cr was also observed by Li et al [19] The rise in the a 0 for a higher concentration of Cr may be due to the fact that instead of trivalent the divalent Cr ion substitutes Fe 2+ in the A-site which results in the increase of lattice constant as the lattice constant of Cr 2+ is larger than that of Fe 2+ [19]. Another possible reason is: the oxides of Cr reside at the grain boundary (as seen from the micro-graphs in section 3.2) thereby obstructing the grain growth and exerts a stress on the unit cell.…”
Section: Methodssupporting
confidence: 79%
“…After x = 0.3, the a 0 rises with increasing Cr content. The rise in the a 0 for a higher concentration of Cr was also observed by Li et al [19] The rise in the a 0 for a higher concentration of Cr may be due to the fact that instead of trivalent the divalent Cr ion substitutes Fe 2+ in the A-site which results in the increase of lattice constant as the lattice constant of Cr 2+ is larger than that of Fe 2+ [19]. Another possible reason is: the oxides of Cr reside at the grain boundary (as seen from the micro-graphs in section 3.2) thereby obstructing the grain growth and exerts a stress on the unit cell.…”
Section: Methodssupporting
confidence: 79%
“…Table 1 shows that the lattice parameter, volume of the unit cell, and tolerance factor are decreased with increasing chromium ion, which is attributed to the ionic radii difference. This trend indicated that the prepared samples are more strained [27].…”
Section: Resultsmentioning
confidence: 80%
“…where α is the absorption coefficient, hν is the energy of the incident radiation, B is a constant known as the band tailing parameter, and E g is the energy bandgap between the top of the valence band and the bottom of the conduction band [27,31].…”
Section: Edx Analysismentioning
confidence: 99%
“…[ 47 ] It is well established that Li 1+ and Cr 3+ ions have site preference for the octahedral sites, and the rest of the ions can occupy both the sites with varying ionic radii for different sites. [ 2,48 ] The lattice parameter for the composition x = 0.01 is higher than the pristine sample, which may be due to the incorporation of larger Li 1+ and Cr 3+ ions at B site replacing Fe 3+ ions.…”
Section: Resultsmentioning
confidence: 97%
“…[47] It is well established that Li 1þ and Cr 3þ ions have site preference for the octahedral sites, and the rest of the ions can occupy both the sites with varying ionic radii for different sites. [2,48] The lattice parameter for the composition x ¼ 0.01 is higher than the pristine sample, which may be due to the incorporation of larger Li 1þ and Cr 3þ ions at B site replacing Fe 3þ ions. This substitution causes increase in the concentration of Fe 3þ ions at A site, which results in the increase of mean ionic radii (r A ) of tetrahedral site and ionic radii (r B ) of octahedral site, which overall increases the lattice parameter.…”
Section: Resultsmentioning
confidence: 98%